2006
DOI: 10.1007/s10310-006-0216-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 13-year fencing on browsing by sika deer on seedlings on Mt. Ohdaigahara, central Japan

Abstract: We examined the effects of fencing on deer browsing on seedlings 13 years after the building the experimental fence on Mt. Ohdaigahara, central Japan, where the sika deer (Cervus nippon) population is high. There was no difference in the species number of seedlings between 1991 and 2004. The density of seedlings in the fenced plot in 2004 was three times higher than in 1991. Although the unfenced plots had no seedlings higher than 20 cm, there were seedlings up to 120 cm in the fenced plot. These results sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 22 publications
3
22
0
Order By: Relevance
“…Sorges (2001) documented that after the establishment of forest stands the trees from natural regeneration inside the fence were significantly taller than the unprotected ones. The same conclusion was drawn by Kumar et al (2006). The influence of these measures is positive, but higher costs of plantation protection are incurred.…”
Section: Introductionsupporting
confidence: 69%
“…Sorges (2001) documented that after the establishment of forest stands the trees from natural regeneration inside the fence were significantly taller than the unprotected ones. The same conclusion was drawn by Kumar et al (2006). The influence of these measures is positive, but higher costs of plantation protection are incurred.…”
Section: Introductionsupporting
confidence: 69%
“…The density of coniferous seedlings in the unfenced plot was 1.3 times higher than in the fenced plot, however, because of the presence of many small seedlings (height < 0.05 m). Kumar et al (2006) reported dense ground vegetation in the fenced plot whereas the ground in the unfenced plot is partly bare, suggesting the establishment of small coniferous seedlings in the unfenced plot is because of the bare ground. We therefore assume that changes in the forest floor after fencing might affect the establishment of new coniferous seedlings.…”
Section: Introductionmentioning
confidence: 94%
“…After 13 years, the overall density of seedlings in the fenced plot was 1.6 times higher than in the unfenced plot (Kumar et al 2006). The density of coniferous seedlings in the unfenced plot was 1.3 times higher than in the fenced plot, however, because of the presence of many small seedlings (height < 0.05 m).…”
Section: Introductionmentioning
confidence: 95%
“…For example, the stripping of bark causes wood decay leading to a decline in forest cover (Akashi and Nakashizuka 1999;Miquelle and van Ballenberghe 1989;Yokoyama et al 2001), while browsing and/or grazing may alter the structure and composition of vegetation on the forest floor (Kumar et al 2006;Rooney and Waller 2003;Schütz et al 2003;Stockton et al 2005;Webster et al 2005). Furthermore, these environmental changes may also have an indirect effect on other organisms in the forest ecosystem Feber et al 2001;Flowerdew and Ellwood 2001;Rooney 2001).…”
Section: Introductionmentioning
confidence: 99%